Study on Employment Pressure on Chinese College Students and Constructing Higher Education Strategies in The Post—Epidemic Era - Huang Xia; Liu Yanqin; Deng Chao; Guo Ying; Xu Yimeng (SHS Web of Conferences)
During the post epidemic era, Chinese university students are confronted with multiple pressures regarding employment, including unprecedented competition, significantly elevated employment thresholds, a pronounced tendency towards limited job options, and a growing number of students with inadequate employability skills. This paper aims to analyze the current employment situation of university graduates and its underlying causes, while proposing corresponding solutions, in an effort to provide a reference for higher education institutions in enhancing their graduate employment education initiatives.